Placental transmogrification of the lung associated with unilateral pleural effusion: A case report with a comprehensive review of the literature - Naureen Narula; Sam Ngu; Dikshya Sharma; Faraz Siddiqui; Michel Chalhoub (Respiratory Medicine Case Reports, 2019)
Placental transmogrification of the lung (PTL) is a rare benign pulmonary lesion resembling chorionic villi. With fewer than 40 cases reported in literature, associations have thus far been made with bullous emphysema, pulmonary fibrochondromatous hamartomas and adenocarcinoma of the lung. Typically presenting as unilateral solitary cystic or bullous lesion, we report the first case of PTL presenting with unilateral pleural effusion. A 70-year-old male presented with recurrent unilateral pleural effusion that failed to resolve with multiple thoracenteses. He underwent thoracoscopic excision and biopsy of a cystic mass identified on computed tomography (CT) scan which revealed characteristic villous and papillary changes. We describe the case and review the literature on this benign but rare pulmonary disease entity.